On topological properties of some convex polytopes by using line operator on their subdivisions. Issue 4 (18th May 2020) - Husin, Mohamad Nazri; Asif, Fatima; Zahid, Zohaib; Zafar, Sohail
Abstract: In this paper, we give theoretical results for some topological indices such as Zagreb indices, Zagreb co-indices hyper-Zagreb index HM ( G ), atom-bond connectivity index ABC ( G ), sum connectivity index ( G ) and geometric-arithmetic connectivity index GA ( G ), by considering G as line graph of subdivision of some convex polytopes and denotes its complement.